Understanding and minimizing risk for strikes in Vietnam - Sunoo, Jan Jung-Min (International Labour Organization, 2007)
The report shows a practical guide for strikes resolves. It is about What are the trends of strikes in Vietnam? Where are strikes occurring and How? Why workers go on strikes? How can employees and employers address the problems of labor relations. What re good practices?